The Mediating Role of Emotion Regulation in the Relationship between Resilience and Marital Conflict - Shamsollahi , Mehri (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the mediating role of emotion regulation in the relationship between resilience and marital conflict. Methods: The study was correlational, and its statistical population consisted of all married women with family disputes who visited counseling centers in Tehran in 2021. The research sample consisted of 200 married women who were selected using two-stage cluster sampling and the simple random method by draws. The research tools included The Difficulties in Emotion Regulation Scale (DERS) by Gratz & Roemer (2004), Connor-Davidson Resilience Scale (CD-RIS) (2003), and Kansas Marital Conflict Scale (KMCS) (1985). The obtained data were analyzed using the chi-square test and path analysis. Results: The path analysis results indicated that there was a direct and significant relationship between resilience and emotion regulation and also between marital conflict and emotion regulation (P=0.05). Furthermore, emotion regulation had a mediating role in the relationship between resilience and marital conflict (P=0.05). Conclusion: The ability to regulate emotion increased and problems such as marital conflicts decreased by promoting resilience. It is suggested holding training programs for promoting resilience and regulating couples' emotions.